Pollen Grain Morphological Characteristics of American Persimmon (Diospyros virginiana L.) - Grygorieva, Olga; Motuleva, Svetlana; Nikolaieva, Nataliia; Klymenko, Svitlana; Schubertová, Zuzana; Brindza, Jan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Morphology of pollen grain was described for nine American persimmons (Diospyros virginiana L.) genotypes (DV-01 – DV-09) at the Institute of Biodiversity and Biological Safety of Slovak Agricultural University in Nitra using an electron microscope Carl Zeiss LS 15, and the microphotographs were taken. The measurement of morphometric parameters was carried out on 50 pollen grains from each genotype using the AxioVision Rel. 4.8.2.0 program. The measurements were made in micrometer (μm). The length of polar axis (P) and the equatorial diameter (E) of grain, P/E ratio were measured and their variation was compared among studied genotypes. The polar axis and equatorial diameter of pollen grains values were varied from 51.94 to 78.60 μm and from 23.00 μm to 42.71 μm, respectively. This study showed that there were significant differences among the genotypes in all measured factors. Pollen grains are radial-symmetrical, isopolar, tricolpate (with three sulcus). Exine surface is a bicomponent sculptural type with small perforate-undulate or wrinkled weakly perforate. Percentages of abnormal pollen grains ranged from 2.0 to 19.3% among the genotypes. It was noted that diversity of surface sculpturing of pollen grains in combination with shape and sizes of them enables to use complex of thin morphologic signs for Diospyros virginiana pollen identification.